SPECIFICITIES OF THE EMPLOYMENT POSITION OF THE DIRECTOR IN A BUSINESS COMPANY - Jašarević, Senad; Božičić, Darko M (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
The question of the labor law position of directors has long attracted the attention of both legal theory and legal practice. However, many aspects of the status of directors still remain unresolved. This is particularly characteristic of his employment status. For this reason, the paper analyzed problematic issues, first of all, in connection with appointment a director, and then in connection with the removing director from the office and the consequences that such removal has on the social and economic position of the person who performed the function of the director. In the end, the modern tendencies with regard to individual clauses, which are an almost indispensable part of the content of the contract regulating the mutual rights, obligations and responsibilities between the director and the company, were reviewed.